Antibacterial activity of Piper betle L. (Piperaceae) and its products - Thuy, Ho Thi Thach Thuy; Tran Do Cong Danh; Dang Thi Le Thuy; Ha, Ly Hong Huong (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Piper betle L. is a common species in many countries and is used in the production of natural products mainly for its antibacterial activity. Objective: To investigate the antibacterial ability of 96%, 70%, 50% ethanol extracts, essential oils, and products from P. betle. Research methods: agar disc diffusion and dilution methods to determine MIC (minimum inhibitory concentration). Results: The extracts and essential oils of P. betle have good effects on 2 strains of bacteria E.coli and S.aureus, in which the extract with the best MIC is 96% ethanol extract (0.312 mg/mL and 0.078 mg/mL for E. coli and S. aureus, respectively). The MICs of essential oils were 0.5% and 0.0312% for E. coli and S. aureus, respectively, while products from P. betle were only active against S. aureus but had no effect on E.coli strains. Conclusion: Extracts, essential oils, and preparations from P.betle have antibacterial activity against two strains of bacteria, E.coli and S.aureus. Research should be directed to other strains of bacteria for more comprehensive evaluation.